Ozonização de líquidos alternativos para produção de óleos com atividade bactericida - Iorio, Fernanda Bispo dos Reis Di [UNIFESP] (2014)
In this work we have shown the ozonation of two new liquids, a mineral oil (Nujol) and an ionic liquid, aiming to obtain oils with ozone in high concentration and for longtime. The ozonation processes were performed during different times for both liquids : 1, 3, 6 , 9 and 15 h for Nujol oil and 1, 3 and 6 h for the ionic liquid. All samples were characterized by infrared spectroscopy (IV), ultraviolet-visible spectroscopy (UV - Vis), thermogravimetry (TG), nuclear magnetic resonance ( 1H , 13C ) and density and viscosity analyses. The ozone concentration in the samples was determined by iodometric titration. Microbiological tests with five species: Enterococcus faecalis, Candida albicans, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa were tested just for the ozonated Nujol oils. It was found that in the Nujol oil, ozone remains for at least 40 days after the ozonation and in the sample ozonated for 15 h, the ozone concentrations was 7.5 mg/mL and the ozonation process did not alter the chemical structure of the oil. In the ionic liquid the ozone concentration was 13,1 mg/mL, which is two times higher than in the Nujol oil and it was not observed any alteration in the chemical composition of the ionic liquid with the ozonation process. The Nujol oil in its pure form showed no antimicrobial activity against the tested microrganisms, however when ozonated it showed antimicrobial activity against the species Enterococcus faecalis , Staphylococcus aureus and Escherichia coli .